The Impact of Attachment on Depression in Married Seniors: Chain Mediating Effects of Self-Esteem and Rumination - Peng, Jiaxi; Zhang, Jiaxi; Zhao, Kangwei; Wang, Xin; Wu, Yi; Fang, Peng; Lv, Jing (Frontiers in Psychology, 2021)
In this study, we aimed to discuss the effects of attachment on depression, and we focused on the mediating roles of self-esteem and rumination in older Chinese adults. A total of 438 older adults were assessed, using Experiences in Close Relationships Inventory, Rosenberg Self-Esteem Scale, Ruminative Responses Scale, and Short Form of Center for Epidemiologic Studies Depression Scale. Both attachment anxiety and attachment avoidance significantly predicted depression in the older adults. Attachment anxiety and attachment avoidance positively predicted rumination but negatively predicted self-esteem. Structural equation models showed that rumination and self-esteem fully mediated the effects of attachment anxiety and attachment avoidance on depression. It can be concluded that the attachment of older adults is related to depression, and that there are chain mediating effects of self-esteem and rumination between attachment and depression.